Analysis of Quality Tests Created by FKIP-UHAMKA Faculty for Middle Semester in Academic Year 2016-2017 - Astuti, Sri; Kusdiwelirawan, Acep; Dahlia, Siti (Program Studi Pendidikan Fisika UHAMKA, 2018)
This research is to analyse the quality of test for midterm examination Academic Year 2016-2017 of FKIP UHAMKA lectures. The aims of the research were to identify the quality of the test on compulsory institutional courses academic year 2016-2017 and to analyse the weakness point of the lectures in the making of quality test based on the analysis of the test for midterm examination academic year 2016-2017. The method that used in this research was descriptive analysis method through documentation as a data collection technique. Subjects of this research were semester plan document (RPS) and items test were arranged by lectures. The data that will be analysed are consist of 6 courses, including essay and multiple choice questions. The object of the research was the quality of the items test considered by a few aspects that were learning achievement of RPS, substance of items test, items test structure, and culture/grammar. The instrument for data collection were rubric and researcher which were as human instrument. Overall, the result of this research was the items test have quality with level moderate to good. Furthermore, the majority of items test have weakness related to the making of items test which were the decription of indicators: the learning achievements (such as attitude, general and particular skills) and score list on the items test.